Analisis Rasio Likuiditas dan Debt to Equity Ratio Sebagai Penilaian Terhadap Kinerja Keuangan Pada Perusahaan Tekstil dan Garmen Yang Terdaftar Di BEI Periode 2020 - Anindia, Elis (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
Financial performance is a form of achievement achieved by the company in managing finances and also describes the condition of an entity's performance. This study aims to determine the simultaneous and partial effect of the Liquidity variable as measured by the Current Ratio (CR) and the Debt to Equity Ratio (DER) variable on financial performance as measured by the Profitability Ratio (ROA). The population used in this research is the annual financial statements of Textile and Garment companies listed on the Indonesia Stock Exchange for the 2020 period. The method used in this research is descriptive research with a quantitative approach. Sample selection using purposive sampling. The sample used is the annual financial statements of Textile and Garment companies listed on the Indonesia Stock Exchange for the 2020 period. The data source in this research is secondary data in the form of audited financial reports obtained from www.idx.co.id. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it was concluded that liquidity and debt to equity ratio simultaneously have a significant effect on financial performance. Partially, liquidity has a significant effect on financial performance. The debt to equity ratio partially does not have a significant effect on financial performance.